Gasoline price cycle drivers: An Australian case study - Bloch, Harry; Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2010)
In many retail gasoline markets, prices follow a saw-toothed cycle first posited by Edgeworth (1925) and formalised by Maskin & Tirole (1988). A growing literature explores driving factors behind such cycles, most particularly in Canada and the US. This paper explores price cycles in a retail gasoline market in Australia with a unique regulatory environment that provides a census of data. We make use of a threshold regression model, and pay particular attention to local market effects and market structure. Both are novel in the study of retail petroleum prices.